THE IMAGE IN THE MIRROR AND THE NUMBER ON THE SCALE: WEIGHT, WEIGHT PERCEPTIONS, AND ADOLESCENT DEPRESSIVE SYMPTOMS - Frisco, Michelle L. (2010)
Double jeopardy and health congruency suggest that adolescents’ joint experience of their weight and weight perceptions are associated with depressive symptoms, but each theory offers a different prediction about which adolescents are at greatest risk. This study investigates the proposed associations and the applicability of both theoretical perspectives using data from 6,557 male and 6,126 female National Longitudinal Study of Adolescent Health (Add Health) Wave II participants. Empirically, results indicate that focusing on the intersection of weight and weight perceptions better shows which adolescents are at risk of depressive symptoms than an approach that treats both predictors as independent, unrelated constructs. Weight pessimists are at greatest risk of depressive symptoms. Thus, results support the health congruency framework, its extension to subpopulations outside of older adults, and its extension to optimism and pessimism about specific health conditions.